The Effect of Transformational Leadership and Organizational Culture on Organizational Commitment in Mediating Organizational Cynicism - Prayudha Bangun Wicaksono Wicaksono; Muafi Muafi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
This study discusses and analyzes the effect of transformational leadership and organizational culture on organizational commitment mediated by organizational cynicism on employees at the Shirvano Consulting Yogyakarta company. The population and sample in this study are 31 respondents who are startup employees at Shirvano Consulting. This research uses quantitative methods by distributing questionnaires to respondents. The analytical test tool used in this study is SmartPLS v.3.0 with SEM analysis method. The results of data analysis in this study are: (1) Transformational leadership has a significant negative effect on organizational cynicism; (2) Organizational culture has no significant negative effect on organizational cynicism; (3) Organizational cynicism has a significant negative effect on organizational commitment; (4) Transformational leadership has no significant positive effect on organizational commitment; (5) Organizational culture has no significant positive effect on organizational commitment; (6) Transformational leadership has no significant positive effect on organizational commitment mediated by organizational cynicism; and (7) Organizational culture has a significant positive effect on organizational commitment mediated by organizational cynicism. Three hypotheses are accepted, while the other four hypotheses are rejected. The implication of the theory is to contribute to increase organizational commitment by considering aspects of transformational leadership and organizational culture by the mediating effect of organizational cynicism. The managerial implication is that companies or organizations can implement strategies and policies related to these four aspects.